Circular Interior Design Strategies For Adaptive Reuse: Enhancing Eco-Conscious Practices In Contemporary Workspace Environments - Myeong, Go eun; Rae, Song Mi; il, Han Jang; Seob, Choi Jung (University of Science and Computer Technology, 2025)
The urgency of ecological sustainability in contemporary interior architecture has intensified due to global environmental challenges and resource depletion. Workspaces significantly contribute to energy consumption, carbon emissions, and material waste, requiring a shift from linear consumption to regenerative, circular practices. This study introduces a Circular Interior Design Strategies Framework that extends beyond conventional certifications (e.g., LEED, BREEAM) by integrating four interdependent pillars: material recirculation, modular adaptability, biophilic integration, and lifecycle-driven decision-making. A qualitative descriptive methodology combining systematic literature review, case-study analysis, and expert validation was employed. Findings demonstrate that adaptive reuse can reduce embodied carbon by 40–70 percent while preserving cultural identity and spatial integrity. The proposed framework clarifies how interior design operationalizes circular economy principles at the design stage rather than post-construction assessment. This study provides a structured framework for designers and policymakers to implement circular strategies effectively, positioning interior design as a proactive agent in sustainable workplace transformation.